Emerging security challenges in cloud computing: An insight to cloud security challenges and their mitigation - Behl, A. (2011 World Congress on Information and Communication Technologies, 2011)
Cloud computing has changed the whole picture that distributed computing used to present e.g. Grid computing, server client computing. Cloud has given a new meaning to distributed, and off-premises computing. Although, Cloud offers great benefits, it also introduces a myriad of security threats to the information and data which is now being ported from on-premises to off-premises. Where cloud computing can help organizations accomplish more by paying less (in the longer run) and breaking the physical boundaries between IT infrastructure and its users, due to openness of accessible information and data relying on trust between cloud provider and customer, heightened security threats must be overcome in order to benefit fully from this new computing exemplar. Breach in the security of any component in the cloud can be both disaster for the organization (the customer) and defacing for the provider. This paper explores the security issues related to the cloud. The paper also discusses the existing security approaches to secure the cloud infrastructure and applications and their drawbacks. Finally, we explore some key research challenges of implementing new cloud-aware security solutions that can provide the likes of pre-emptive protection for complex and ever dynamic Cloud infrastructure, followed by conclusion where we try to entail the whole research and try to formulate a security strategy which will enable the Cloud providers and customers alike to fight against ever emerging security threats.